Application of piezoelectric materials as sensor and actuator for aeroelastic investigation - Éder Luiz Oliveira (2014)
This dissertation aims to apply piezoelectric materials as actuator and sensor to perform aeroelastic analysis. Two semi-span wing models based on flat plates with different characteristics were tested using PZT (Lead Zirconate Titanate) as actuator, PVDF (Polyvinylidene Fluoride) as sensor and the results were compared with vibrometer laser results. An aluminum model with a ballast on the wing tip, whose its location can be modified was tested in experimental modal analysis. Using the aluninum model, an investigation about aeroelastic behaviour was conducted in wind tunnel and the V-g/V-f diagram determined. This diagram shows the aeroelastic evolution of the natural frequencies and damping as function of speed (or dynamic pressure). In this aeroelastic analysis, the ability of the PVDF in determining the V-g/V-f diagram was evaluated. A numerical model of composite flat plate was generated considering the piezoelectric instrumentations. The second specimen tested corresponds to composite wing models that are based on laminate composite flat plate. Five models with different fiber orientations were tested in (pure) experimental modal analyses and wind tunnel, hence, the capability of excitation of PZT was verified. Good results were obtained regarding the estimation of natural frequency and damping factor using a single PVDF element. The application of PZT as actuator in the wind tunnel test showed improvement on the data acquisition in terms of noise. However, were observed some characteristics that require careful. As support to experimental tests, several studies were performed.